Association of maize (Zea mays L.) senescence with water and nitrogen utilization under different drip irrigation systems - Wu, Yang; Yao, Fanyun; Wang, Yongjun; Ma, Lin; Li, Xiangnan (Frontiers in Plant Science, 2023)
Drip irrigation is an efficient water-saving system used to improve crop production worldwide. However, we still lack a comprehensive understanding of maize plant senescence and its association with yield, soil water and nitrogen (N) utilization under this system. Thus, a 3-year field experiment in the northeast plains of China was used to assess four drip irrigation systems: (1) drip irrigation under plastic film mulch (PI), (2) drip irrigation under biodegradable film mulch (BI), (3) drip irrigation incorporating straw returning (SI), (4) drip irrigation with the tape buried at a shallow soil depth (OI), and furrow irrigation (FI) was used as the control. The plant senescence characteristic based on the dynamic process of green leaf area (GLA) and live root density (LRLD) during the reproductive stage, and its correlation with leaf N components, water use efficiency (WUE) and N use efficiency (NUE) were investigated. PI followed by BI achieved the highest integral GLA and LRLD, grain filling rate, and leaf and root senescence rate after silking. Greater yield, WUE and NUE were positively associated with higher N translocation efficiency of leaf protein responding for photosynthesis, respiration, and structure under PI and BI. While, no significant differences were found in yield, WUE and NUE between PI and BI. SI effectively promoted LRLD in the deeper 20-100 cm soil layers, prolonged the GLA and LRLD persistent durations, and reduced the leaf and root senescence rates. The remobilization of non-protein storage N was stimulated by SI, FI, and OI, which made up for the relative inadequacy of leaf N. In summary, instead of persistent GLA and LRLD durations and high translocation efficiency of non-protein storage N, fast and large protein N translocation from leaves to grains under PI and BI was found to facilitate maize yield, WUE and NUE in the sole cropping semi-arid region, and BI was recommend considering it can reduce plastic pollution.